The GRIA3 c.2477G > A Variant Causes an Exaggerated Startle Reflex, Chorea, and Multifocal Myoclonus. Issue 7 (5th May 2020) - Piard, Juliette; Béreau, Matthieu; XiangWei, Wenshu; Wirth, Thomas; Amsallem, Daniel; Buisson, Lauren; Richard, Philippe; Liu, Nana; Xu, Yuchen; Myers, Scott J.; Traynelis, Stephen F.; Chelly, Jameleddine; et al.
Abstract: Background: Hemizygous mutations in GRIA3 encoding the GluA3 subunit of the amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor are known to be associated with neurodevelopmental disorders, including intellectual disability, hypotonia, an autism spectrum disorder, sleep disturbances, and epilepsy in males. Objective: To describe a new and consistent phenotype in 4 affected male patients associated with an undescribed deleterious variant in GRIA3 . Methods: We evaluated a large French family in which segregate a singular phenotype according to an apparent X‐linked mode of inheritance. Molecular analyses using next generation sequencing and in vitro functional studies using 2‐electrode voltage clamp recordings on Xenopus laevis oocytes and a β‐lactamase reporter assay in transfected human embryonic kidney (HEK293) cells were performed. Results: In addition to mild intellectual disability and dysarthria, affected patients presented a tightly consistent early‐onset movement disorder combining an exaggerated startle reflex with generalized chorea and multifocal myoclonus. The unreported GRIA3 missense variant c.2477G > A; p.(Gly826Asp) affecting the fourth transmembrane domain of the protein was identified in index patients and their unaffected mothers. Functional studies revealed that variant receptors show decreased current response evoked by agonist (ie, kainic acid and glutamate) and reduced expression on the cell surface in favor of pathogenicity by a loss‐of‐function mechanism. Conclusions: Taken together, our results suggest that apart from known GRIA3 ‐related disorders, an undescribed mutation‐specific singular movement disorder does exist. We thus advocate considering GRIA3 mutations in the differential diagnosis of hyperekplexia and generalized chorea with myoclonus. © 2020 International Parkinson and Movement Disorder Society